1993
DOI: 10.1113/expphysiol.1993.sp003691
|View full text |Cite
|
Sign up to set email alerts
|

Motor units within the normal rat medial gastrocnemius

Abstract: SUMMARYThe contractile properties, fatiguability and axonal conduction velocity were

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
2
5
0
Order By: Relevance
“…P tw :P tet was higher in FF than in S, FR, or FI motor units. Previous studies found similar differences between FF and S motor units in twitch:tetanus ratio, but all F units had similar values (Celichowski and Grottel 1993;Einsiedel and Luff 1993). A greater degree of twitch potentiation (i.e., lower P tw :P pot ratio) was seen in F than in S motor units; this was FIG. 11.…”
Section: Relationship Between Sag and Other Motor Unit Propertiessupporting
confidence: 54%
See 3 more Smart Citations
“…P tw :P tet was higher in FF than in S, FR, or FI motor units. Previous studies found similar differences between FF and S motor units in twitch:tetanus ratio, but all F units had similar values (Celichowski and Grottel 1993;Einsiedel and Luff 1993). A greater degree of twitch potentiation (i.e., lower P tw :P pot ratio) was seen in F than in S motor units; this was FIG. 11.…”
Section: Relationship Between Sag and Other Motor Unit Propertiessupporting
confidence: 54%
“…Stimulation at 40 Hz is the de facto standard of motor unit typing in cats (Burke et al 1973). However, CT tw of TS motor units is substantially shorter in rats (Bakels and Kernell 1993b;Chamberlain and Lewis 1989;Einsiedel and Luff 1993;Gardiner 1993;Grottel and Celichowski 1990) than that in cats (Burke 1967;Burke et al 1973;Proske and Waite 1974;Wuerker et al 1965). Therefore a higher stimulation frequency was chosen to maintain a comparable degree of tetanic fusion.…”
Section: Electrophysiological Recordingmentioning
confidence: 99%
See 2 more Smart Citations
“…Einsiedel and Luff,22 in physiological studies of the functional characteristics of motor units, described ‘ the existence of a motor unit continuum ’. They found that from the smallest fatigue-resistant slow units to the larger fast-fatiguable units, ‘ an almost continuous range of fatigue resistance and motor unit force exists ’.…”
Section: Histochemical Muscle Fibre Types: Are the Assumptions Correct?mentioning
confidence: 99%